2013
DOI: 10.1080/17496535.2013.768071
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Ethical Non-Sequiturs in Botswana's HIV and AIDS Policies: Harmonising the Halo Effect

Abstract: Like many African countries, Botswana is adversely affected by HIV and AIDS. However, from the onset of the epidemic there was an inimical expectation, both internally and externally, that the country would effectively address the problem. The paper posits that this expectation was a partial result of the halo effect emanating from Botswana's successful history on many social, economic, and political fronts. However, whilst the country's HIV and AIDS strategy is one of the success stories of the African contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…additional stigmatisation and marginalization. They may also become subject to deportation, imprisonment or extortion in exchange for short-term visas (49). Obtaining consent can inhibit participation due to privacy and identification issues related to their undocumented status.…”
Section: Box 1: Migration In Botswanamentioning
confidence: 99%
“…additional stigmatisation and marginalization. They may also become subject to deportation, imprisonment or extortion in exchange for short-term visas (49). Obtaining consent can inhibit participation due to privacy and identification issues related to their undocumented status.…”
Section: Box 1: Migration In Botswanamentioning
confidence: 99%
“…These results suggested that a negative description reduces the attractiveness halo effect in men when rating the qualities of an attractive woman. English, Irons, & Henslee, 2013), impact of interpersonal skills of service employees (Dagger, Danaher, Sweeney, & McColl-Kennedy, 2013), perceptions of athletes using steroids (Chantal, Bernache-Assollant, & Schiano-lomoriello, 2013), impact of the phrase "natural ingredients" on perfume perception (Apaolaza, Hartmann, López, Barrutia, & Echebarria, 2014), and expectations of a country's response to AIDS/HIV (Jacques, & Mmatli, 2013). For example, past studies have revealed that the halo effect often occurs when teachers grade their students' papers.…”
Section: Spring 2016 Psi Chi Journal Of Psychological Researchmentioning
confidence: 99%
“…Impact of Descriptors on Halo Effect | Lammers, Davis, Davidson, and Hogue English, Irons, & Henslee, 2013), impact of interpersonal skills of service employees (Dagger, Danaher, Sweeney, & McColl-Kennedy, 2013), perceptions of athletes using steroids (Chantal, Bernache-Assollant, & Schiano-lomoriello, 2013), impact of the phrase "natural ingredients" on perfume perception (Apaolaza, Hartmann, López, Barrutia, & Echebarria, 2014), and expectations of a country's response to AIDS/HIV (Jacques, & Mmatli, 2013). For example, past studies have revealed that the halo effect often occurs when teachers grade their students' papers.…”
Section: Impact Of Positive Negative and No Personality Descriptorsmentioning
confidence: 99%